Evaluation of Optical Coherence Tomography Angiography Parameters following Intravitreal Ranibizumab Biosimilar in Diabetic Macular Oedema - Sodhi, Punita Kumari; Rana, Aman Singh; Doddaiah, Divya; Dipta, Shreyangshi; Mahajan, Bhawna; Banerjee, Bratati (Nepalese Journal of Ophthalmology, 2026)
Introduction: Ranibizumab biosimilar (RbB) has emerged as a cost-effective treatment modality. There is paucity ofliterature on optical coherence tomography angiography (OCTA) parameters following use of RbB in DME.Objective: To evaluate OCTA parameters following intravitreal ranibizumab RbB in DME.Methodology: In an interventional study on treatment naïve eyes having DME, ocular examination for best-corrected visual acuity (BCVA), intraocular pressure (IOP), colour vision (CV) and contrast sensitivity (CS) was done. Further, optical coherence tomography (OCT) measured central foveal thickness (CFT). The OCTA imaging examined the foveal avascular zone (FAZ) and vessel density (VD) in six layers, including superficial capillary plexus (SCP), deep capillary plexus (DCP), outer retina (OR), outer retinal chorio-capillaries (ORCC), chorio-capillaries (CC) and choroid (C). Serum vascular endothelial growth factor-A (VEGF-A) levels were measured using an enzyme-linked immunosorbent assay (ELISA). One month after 0.5 mg/0.05 ml intravitreal injection of RbB, pre- and post-treatment parameters were compared.Result: The study involved 44 eyes of 30 DME patients having a mean age of 56.0±8.66 years. The mean serum VEGFA levels were 539.11±336.44 pg/ml. Following treatment, the mean CFT reduced from 461.50±173.06 to 348.09±153.02microns (p